Egocentricity in the English Generic Pronouns: Semantics and Pragmatics - Tonyan, Marika (Armenian Folia Anglistika, 2005)
The article analyses the self-centered semantic component of generic pronouns. The examination of the nature and content of this component in the present article is based on surveys with language bearers. The presence of the meaning described explains the pragmatic and stylistic applications of these pronouns, particularly their linguistic-demagogic function which aims to exert a direct impact on the listener.